Definition desired mode ultraviolet radiation, which prevent Mycobacterium tuberculosis survival and conversion to L-forms - Moiseenko, T; Volyanski, A; Kovaleva, A (Annals of Mechnikov's Institute, 2020)
Bactericidal effect of ultraviolet (UV) rays was first described over 100 years ago. UV was used in hospitals from 1930 and in 1936 was first used to sterilize the air in the operating room. The maximum bactericidal effect occurs in the region 254-257 nm UV wavelength, which is manifested mainly in the destructive-modifying photochemical damage of DNA synthesis. So, UV rays causes an increase in the permeability of the microbial cell membranes to ions environment and coagulation of colloids cytoplasm, resulting in disruption of normal cell development, stopping the reproduction and lysis. In any body there are biochemical mechanisms that could fully or partially restore the damaged original structure of the DNA molecule - fotoreactivation. It's resistant microorganisms consist about 0.01% of the microbial population, but the certain types reach 1-5%. Surviving bacteria can form new colonies with less susceptibility to radiation. Mycobacteria in the course of evolution developed various mechanisms to overcome or inactivation of adverse environmental factors: a special cell wall (waxes, fats, mycolic acid); large metabolic capabilities by which M. tuberculosis able to inactivate various antiseptics and disinfectants; morphological plasticity, which is spontaneous and induced transformation in L-forms with a reversion of virulent original shape. М. tuberculosis more resistant to UV radiation than other bacteria. Materials and methods. We investigated the effectiveness of UV radiation against to M. tuberculosis at distances from the radiator - 70 cm, 140 cm, 210 cm; exposure time 20, 30, 40 and 50 minutes. We used museum strain H37Rv and 3 clinical strains: 1 - strain with preserved sensitivity; 2 - strain with resistance to isoniazid and rifampicin; 3 - strain with resistance to isoniazid, rifampicin and ofloxacin (enhanced resistance). We used radiator - Philips TUV power 30 W (without ozone for up to 6000 hours). Control and irradiated cultures of the pathogen were grown in the media of Levenstain-Yensen, Blood media of Shkolnikova and medium VCG to detect L-forms. For the accuracy of the results, each experiment was performed in 6 series was set down three times (at intervals of 30 days). Results and discution. UV using for 20 minutes almost 1/5 of M. tuberculosis it caused survival (21,60 ± 1,83%); at 30-minute UV (standard exposure time) - 13% M. tuberculosis remain viable; 3,24 ± 1,28% remain viable even 40 minutes of ultraviolet irradiation. Оnly by increasing the time to 50 minutes to achieve sufficient efficacy in destroying vegetative forms, but even this term may not be enough to prevent the formation and survival of L-form (1,08 ± 0.91% in the medium VCG). The effective exposure time vegetative forms of мycobacterium 40 minutes at a distance of 70 cm, at least 50 minutes at a distance of 210 cm. The effective exposure time to prevent the survival of L-form is at least 50 minutes at a distance of 70 cm. Conclusion. The UV irradiation causes the L-transformation of the bacteria. This phenomenon detected on VKG media. The formation of L-forms and the possibility of reversion to consider when using UV. Among the experimental crops more resistant compared to the referent strain differed clinical isolates with the presence of resistance to anti-TB drugs.